Uptake mechanisms of selenium oxyanions during the ferrihydrite-hematite recrystallization. (1st June 2017) - Börsig, Nicolas; Scheinost, Andreas C.; Shaw, Samuel; Schild, Dieter; Neumann, Thomas
Abstract: Se is an essential nutrient at trace levels, but also a toxic environmental contaminant at higher concentrations. The mobility of the trace element Se in natural environments is mainly controlled by the occurrence of the highly soluble Se oxyanions – selenite [Se(IV)] and selenate [Se(VI)] - and their interaction with geological materials. Since iron oxides are ubiquitous in nature, many previous studies investigated Se retention by adsorption onto iron oxides. However, little is known about the retention of Se oxyanions during the formation process of iron oxides. In this paper, we therefore studied the immobilization of Se oxyanions during the crystallization of hematite from ferrihydrite. In coprecipitation studies, hematite was synthesized by the precipitation and aging of ferrihydrite in an oxidized Se(IV)- or Se(VI)-containing system (pH 7.5). Hydrochemical data of these batch experiments revealed the complete uptake of all available Se(IV) up to initial concentrations of c(Se)0  = 10 −3  mol/L ( m / V ratio = 9.0 g/L), while the retention of Se(VI) was low (max. 15% of c(Se)0 ). In case of high initial Se(IV) concentrations, the results also demonstrated that the interaction of Se with ferrihydrite can affect the type of the final transformation product. Comparative adsorption studies, performed at identical conditions, allowed a distinction between pure adsorption and coprecipitation and showed a significantly higher Se retention by coprecipitation than by adsorption. Desorption studies indicated that Se coprecipitation leads to the occurrence of a resistant, non-desorbable Se fraction. According to time-resolved studies of Se(IV) or Se(VI) retention during the hematite formation and detailed spectroscopic analyses (XPS, XAS), this fraction is the result of an incorporation process, which is not attributable to Fe-for-Se substitution or the Se occupation of vacancies. Se initially adsorbs to the ferrihydrite surface, but after the transformation of ferrihydrite into hematite, it is mostly incorporated by hematite. In systems without mineral transformation, however, Se remains as a sorption complex. In case of Se(VI), an outer-sphere complex forms, while Se(IV) forms a mixture of bidentate mononuclear edge-sharing and bidentate binuclear corner-sharing inner-sphere complexes. The results of this study demonstrate that incorporation of Se oxyanions by hematite is an important retention mechanism in addition to pure adsorption, which may affect the migration and immobilization of Se oxyanions in natural systems or polluted environments.